Synthesis and characterization of partially biobased aromatic (Co)polycarbonates containing biphenylene units and pendant pentadecyl chains - Ichake, Amol B.; Nagane, Samadhan S.; Jadhav, Uday A.; Torris, Arun; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (Macromolecular Chemistry and Physics, 2022)
2-Pentadecyl-[1,1''-biphenyl]-4,4''-diol (PBD) is synthesized starting from cashew nut shell liquid-a by-product of cashew processing industry. A new series of partially biobased aromatic (co)polycarbonates possessing biphenylene units and pendant pentadecyl chains is synthesized by solution polycondensation of PBD or varying compositions of PBD and bisphenol-A with triphosgene in dry dichloromethane. Inherent viscosities and number average molecular weights of (co)polycarbonates are in the range 0.51-1.24 dL g(-1) and 18 x 10(3)- 43.4 x 10(3) g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. Flexible, transparent, and free-standing films of (co)polycarbonates can be cast from chloroform solution. (Co)polycarbonates are characterized using Fourier transform infrared spectroscopy (FTIR), H-1 NMR, C-13 NMR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric analysis. T-10 and T-g values of (co)polycarbonates are in the range 417-433 and 8-147 degrees C, respectively. It is demonstrated that the T-g values can be tuned by incorporation of appropriate mol% of PBD as a comonomer in Bisphenol-A-based copolycarbonates. The lowering of the T-g values of (co)polycarbonates can be attributed primarily to the packing disruptive effect of flexible pentadecyl chains. Furthermore, the effect of incorporation of PBD as a comonomer on water contact angle values of (co)polycarbonates is evaluated.
Keywords: aromatic polycarbonates; biobased bisphenol; Cashew nut shell liquid; pentadecyl chain; Renewable resources